Renal Paratransplant Hernia: A Rare Complication of Renal Transplantation - Kunal Vinayak; Abhinandan Mukhopadhyay; Shivam Mishra; Varun Mittal (Indian Journal of Transplantation, 2025)
Renal paratransplant hernia (RPH) is a rare type of internal hernia. There may be a delay in diagnosis due to an ambiguous clinical picture, which leads to significant morbidity. Management using an open surgical approach adds to the morbidity. We report a case of obstructed RPH which was treated promptly with minimally invasive technique. We aim to create clinical awareness about this rare diagnosis of common postoperative symptoms. A 56-year-old gentleman presented to us 1 month after kidney transplant with features of small bowel obstruction. Medical management was unsuccessful. Imaging showed herniation of the ileal loop into the abdominal wall with obstruction. A herniated small bowel loop in the retroperitoneal space through a peritoneal defect was seen. The loop was reduced laparoscopically and the peritoneal defect was not closed but simply incised and widened. Possible mechanisms of RPH formation are either iatrogenic defects of the peritoneum or spontaneous intraperitoneal rupture of lymphoceles. Due to immunosuppression, peritoneal signs may get masked hence the threshold for thoroughly investigating patients should be low. Minimally invasive techniques should be offered to these patients if there are no obvious contraindications.